(3GdeNJUQ ef cJGH GdCOhjI GdeaQOIs - (3eLghds ((3eMeO Hf CMeO eMeO Hf GdTjN HQgGf GdOjf GdeGdci GdNRQLi GdHQOjSi s)
(3ChdgG (B:s
(3eHJhQ GdChd de jcf eYg Mei hjSgd GdWHjYI HCNdGW HdZjI s
(3BNQgG (B:s
(3bTQ CUd GdjfHhJ jaJJ GdCSfGf GdYafI hjfaY ef hLYgG hjbdYgG HdG MOjO fLR eNJUQ s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdWHs